Influence analysis of slot parameters and high torque density optimisation for dual redundant permanent magnet motor in aerospace application. Issue 7 (1st May 2020) - Xu, Jinquan; Zhang, Boyi; Kuang, Xiaolin; Guo, Hong; Guo, Si
Abstract : This study proposes an optimisation approach of high torque density with guaranteed anti‐short‐circuit performance for the dual redundant permanent magnet synchronous motor (PMSM) in an aerospace application. The 10‐pole/12‐slot dual redundant PMSM with concentrated single‐layer windings is firstly proposed, which can restrain the short‐circuit current by the slot design to increase the phase inductance. Since the anti‐short‐circuit design may result in the torque density degradation of the dual redundant PMSM, the influence of the slot parameters on the torque performance of the dual redundant PMSM is thoroughly investigated, including the electromagnetic torque, braking torque, and no‐load torque. Furthermore, the genetic algorithm‐based optimisation method is proposed to maximise the torque density of the dual redundant PMSM, while the anti‐short‐circuit performance can also be guaranteed. Simulation and experimental results are conducted to verify the effectiveness of the proposed optimisation method.